Celastrol Alleviates Autoimmune Hepatitis Through the PI3K/AKT Signaling Pathway Based on Network Pharmacology and Experiments - Wang, Shuhui; Huang, Zheng; Lei, Yu; Han, Xu; Tian, Dean; Gong, Jin; Liu, Mei (Frontiers in Pharmacology, 2022)
Objective: To explore the potential targets and the underlying therapeutic mechanisms of celastrol to autoimmune hepatitis (AIH) by network pharmacology and experiments on Laboratory Animals. Methods: We constructed drug-target interaction network to predict the potential targets of celastrol and the possible association between those targets and the drug; docking studies were also performed to validate ties. Both acute and chronic rodent models of autoimmune hepatitis were used. Gross appearance of liver and spleen were collected, hematoxylin and eosin staining was performed with Sirius red staining to assess hepatic inflammation and fibrosis. Combining molecular docking and enrichment analysis results, we selected the most prominent signaling pathway and further confirmed by western blot in celastrol administrated AIH models. Result: In this study, 82 common targets of celastrol and AIH were obtained from databases, identified by network pharmacology, and also enriched adequately. Among which, PIK3R1, SRC, MAPK1, AKT1 and HRAS were picked as the top 5 closely related targets to celastrol. They all performed well in molecular docking, with AKT1 and PIK3R1 exhibiting more-prominent binding energy. Subsequently, we revealed that celastrol administration significantly ameliorated hepatitis and liver fibrosis by reducing AKT1 and PI3K phosphorylation in both the acute liver injury models and chronic models of autoimmune hepatitis. Conclusions: The present results indicated that celastrol significantly attenuated autoimmune hepatitis by suppressing the PI3K/AKT signal pathway, verified by validated animal models. This study may help illustrate the mechanism involved in the anti-inflammation action of celastrol in autoimmune hepatitis, lay a foundation and provide ideas for future in-depth studies.